2006
DOI: 10.1073/pnas.0604213103
|View full text |Cite
|
Sign up to set email alerts
|

Cyclobutane pyrimidine dimers are predominant DNA lesions in whole human skin exposed to UVA radiation

Abstract: Solar UV radiation is the most important environmental factor involved in the pathogenesis of skin cancers. The well known genotoxic properties of UVB radiation (290 -320 nm) mostly involve bipyrimidine DNA photoproducts. In contrast, the contribution of more-abundant UVA radiation (320 -400 nm) that are not directly absorbed by DNA remains poorly understood in skin. Using a highly accurate and quantitative assay based on HPLC coupled with tandem mass spectrometry, we determined the type and the yield of forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
574
8
10

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 585 publications
(617 citation statements)
references
References 64 publications
25
574
8
10
Order By: Relevance
“…This demonstrated that approximately 50 % of the damage revealed by hOGG1 comet was ALS, levels of which were also statistically significant (P<0.0001), compared to the corresponding control (CSI + 6-TG -hOGG1). Consistent with a recent report [13], we noted essentially no 8-oxodG formation in cells treated with UVA alone, likewise we saw no formation of ALS, not least due to the dose used ( Figure 1A). Whilst treatment of HDFs with 1 M 6-TG, in the absence of UVA, failed to produce any damage, as determined by the alkaline comet assay; when hOGG1 was employed, significant levels of damage were revealed (P<0.0001, compared to CSI + hOGG1).…”
Section: Induction Of 8-oxodg In Cellular Dnasupporting
confidence: 93%
See 3 more Smart Citations
“…This demonstrated that approximately 50 % of the damage revealed by hOGG1 comet was ALS, levels of which were also statistically significant (P<0.0001), compared to the corresponding control (CSI + 6-TG -hOGG1). Consistent with a recent report [13], we noted essentially no 8-oxodG formation in cells treated with UVA alone, likewise we saw no formation of ALS, not least due to the dose used ( Figure 1A). Whilst treatment of HDFs with 1 M 6-TG, in the absence of UVA, failed to produce any damage, as determined by the alkaline comet assay; when hOGG1 was employed, significant levels of damage were revealed (P<0.0001, compared to CSI + hOGG1).…”
Section: Induction Of 8-oxodg In Cellular Dnasupporting
confidence: 93%
“…CPD and pyrimidine (6-4) pyrimidone photoproducts are widely considered to be the lesions responsible for mutagenicity of solar UVR [44], an argument strengthened by the growing evidence that pure UVA can also induce CPD [13,33].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…So a 3-photon process from the laser would result in absorption between 233-267 nm, lying in UVC region, resulting in CPD production. However, the role of UVA component (320-400 nm) in forming CPDs has only been recently confirmed [32,33]. Therefore, 2-photon processes, with absorption between 350-400 nm, can also lead to CPD formation.…”
Section: Role Of Sunlight Uv and Multi-photon Processes In The Risk Mmentioning
confidence: 99%